The Influence of Accounting Information Systems and Internal Control on Employee Performance (Case Study at PT Sriwijaya Distribusindo Raya) - Putri Puji Lestari; Harsi Romli; Leriza Desitama Anggraini (International Journal of Community Service & Engagement, 2022)
This study aims to analyze the effect of accounting information systems and internal controls on employee performance at PT Sriwijaya Distribusindo Raya. The data used in this study were obtained from observation, literature study, and questionnaires. There were 47 respondents in this study. The data collected was then analyzed using multiple linear regression. The results showed that the accounting information system variabel, internal control had a positive effect on employee performance. This research is expected to provide benefits for companies to pay more attention to accounting information systems and internal controls to improve employee performance.